FE Modeling for Bolted Wood Connection Using a Porous Constitutive Model - Huazhang Zhou; Xiaoqiang Zhou (Advances in Civil Engineering)
According to the facts of localized crushing failure of bolt groove in wood connection with enough end distance and the three-phase composites of wood with solid (wood substance), water, and gas, a confined compression test for the wood cylinder was conducted for achieving constitutive relation under the complex stress state in wood groove. A porous constitutive model was developed according to the confined compression experiments. Then, the constitutive model was implemented in a finite element modeling of mental dowel-type fasters in wood-to-wood connections to analyse the load-carrying capacity parallel to the grain. Through changing the thicknesses of centre members and side members of wood connections made of a similar wood species, Pinus Sylvestris var. Mongolica, the effects of thickness combinations of centre members and side members on the failure modes and load-carrying capacity of bolted wood connection including numerical simulations and experiments were compared. The failure modes, including the yielding of centre member, the yielding of side member, and the yielding of the bolt, as well as the rigid rotation of the bolt, all reappeared by the finite element modeling with the porous constitutive model. The predicted deformation shapes and load-displacement relations of bolted wood connections were compared with experimental ones, and good correlations were observed. This paper presents a new approach to simulate the local embedment crushing of bolt groove in wood connections.